Service Quality and Customer Loyalty: The Mediating Effect of Customer Brand Identification in the Nigerian Hospitality Industry - Silas Gontur; Paul Dung Gadi; Esther Bagobiri (International Journal of Marketing & Human Resource Research, 2022)
The hospitality industry performs a significant role in promoting the development of a country’s economy. It is seen as the leading huge revenue earner in the service industry. This study is designed to establish the responsibility of customer product identification in mediating the link between service quality and customer loyalty of hotels in Plateau State. The research adopted a quantitative technique, and data were collected through a survey technique and then analyzed using SPSS. SPSS version 23 was used to determine the potency of the developed variables of the investigation, while the same analytical tool was also utilized to assess the validity and reliability of the variables. Based on the findings of this current study, all proposed hypotheses were proven significant. The finding buttresses the significance of service quality in enhancing customers’ loyalty and brand identification, similarly, customer brand identification correlates significantly with customer brand loyalty. The study also revealed that customer brand identification mediated the link between service quality and client loyalty in the hotel industry in Plateau State. Centered on the outcomes of this investigation, we conclude that perceived service quality does influence customer brand identification, which precedes customer brand loyalty in the hotel subsector. We, therefore, recommend that hotel owners must build up and employ market-oriented service tactics to ascertain customers’ desires and hopes in line to serve the customers better. Furthermore, hotel owners should evaluate service quality frequently to guarantee that they are constantly experiencing the expectations of customers, and contemplate modifying their products and services to improve brand identity and loyalty.